Design of Bidirectional Dc/Dc Converter for Electric vehicle using Split Battery Charging/Discharging - N.Karthieswaruba, Dr.R.Arulmozhiyal, Mr.M.Murali (International Journal of Advanced Science and Technology, 2020)
In this paper a soft-switching bidirectional converter using a lossless with active driver circuit has been proposed. Proposed converter performsZVS (Zero Voltage Switching) of the main switches and ZCS (Zero Current Switching from auxiliary switches obtained to maintain stability in converter. In addition, by utilizing the active driver circuit, issues on reverse-recovery problem of the intrinsic body diodes of the switches are reduced. Driver circuit needs to operate in a short duration; the improved conduction loss of the proposed converter is relatively lower than the conventional soft-switching bidirectional converter. Thus, the overall efficiency improvement achieved over a wide range of load. Moreover, by adjusting according to loads, it is possible to achieve optimized overall efficiency throughout the whole loading range. Real time, the DC motor has been speed controlled by the duty cycle of the switches. Aintegratedcontroller has been designed and simulated for the control of the both the modes i.e. motoring as well as scope of simulation in MATLAB.